A Writing activity kit to complement the fifth years book in the Daniel Córdova High School - Astudillo, Iván; Tinizhañay, Danilo
In the following project we want to present a group of additional activities that will help the writing skill of the students from the fifth grade who use the book Our World Through English. Our investigation is founded in the practice of daily writing by focusing the students´ interests with the use of the following instruments: web pages, e-mail, videos, diary, story books, the English corner, notice board, and brochure. Our methodology follows the basic steps of writing which are first, prewriting where the students gather the ideas for writing; second, drafting where the students choose important information for the paper; third, revising where the students decide what is really the most valuable information to write; fourth, editing where the students have the opportunity to correct mistakes in the content; and finally, publication, where the students have the chance to share their work with others. These activities don´t change the methodology of the book but improves the management of it. We are based on the constructive theory which highlights the importance of the studentsï interaction with their context and society; this way they can learn with the help of their partners and foreign people as well